Impact of extubation failure on the duration of mechanical ventilation in the pediatric population - Thamires de Carvalho Silvério; Cristiane do Prado; Milena Siciliano Nascimento (Einstein (São Paulo))
ABSTRACT Objective To compare the epidemiological profiles of patients who experienced extubation failure with those who achieved success and to evaluate the impact of extubation failure on total mechanical ventilation duration. Methods An observational study with both retrospective and prospective components was conducted on patients admitted to the Pediatric Intensive Care Unit of a private hospital. This study included patients who underwent mechanical ventilation and were extubated between January 2017 and December 2022. Patients were classified into extubation Success or Failure Groups, with failure defined as requiring a return to invasive mechanical ventilation within 48hs post-extubation. Epidemiological factors, including age, pre-existing illnesses, and time on invasive mechanical ventilation, were analyzed. Results A total of 173 patients were included, of which 9 (5.2%) required reintubation within 48hs. The total duration of mechanical ventilation differed significantly between the Success Group (3 days [1.8; 6.6]) and the Failure Group (6.5 days [5.6; 9.3]), p=0.004. Upper airway obstruction was identified as the primary cause of extubation failure. Conclusion This study demonstrated that extubation failure doubled the total duration of mechanical ventilation compared to successful extubation. These findings highlight the importance of daily patient assessment with clearly defined clinical criteria to ensure mechanical ventilation is discontinued precisely when the patient is ready-neither prematurely nor excessively delayed.